2018
DOI: 10.2337/dc17-1852
|View full text |Cite
|
Sign up to set email alerts
|

Associations of General and Central Adiposity With Incident Diabetes in Chinese Men and Women

Abstract: Among relatively lean Chinese adults, higher adiposity-general and central-was strongly positively associated with the risk of incident diabetes. The predicted continuing increase in adiposity in China foreshadows escalating rates of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 36 publications
7
73
1
1
Order By: Relevance
“…In contrast to the J‐shaped relationship of BMI with adverse outcomes, abdominal obesity measured by the waist circumference was found to linearly associate with cardiovascular disease mortality in Europeans . This relatively newer measure of adiposity, which reflects central obesity, was found to associate more strongly with diabetes risk, especially in “thin” Chinese, Koreans, and other Asians. This may explain their propensity to “obesity” and its adverse outcomes despite less elevated BMI.…”
Section: Introductionmentioning
confidence: 83%
“…In contrast to the J‐shaped relationship of BMI with adverse outcomes, abdominal obesity measured by the waist circumference was found to linearly associate with cardiovascular disease mortality in Europeans . This relatively newer measure of adiposity, which reflects central obesity, was found to associate more strongly with diabetes risk, especially in “thin” Chinese, Koreans, and other Asians. This may explain their propensity to “obesity” and its adverse outcomes despite less elevated BMI.…”
Section: Introductionmentioning
confidence: 83%
“…As early as 2009, they suggested that the best range to predict hypertension were 87 cm in men and 80 cm in women, and increasing WC over time could be the cause of the difference. The worldwide upward trend in obesity has been dramatic; from 2013 to 2018, the mean WC increased from 82 cm to 86.3 cm for men and from 79.1 cm to 83.4 cm for older women [32]. However,lower appropriate level were suggested by previous studies [33,34], and ethnic and racial differences might explain the discrepancy between different studies.…”
Section: Discussionmentioning
confidence: 87%
“…Nowadays, more and more attention has been paid to sleep duration among the individuals with obesity [3]. Sleep deprivation among students is regarded to be related to increased risk of obesity, injuries, behavior problems, attention-de cit disorder, poor academic performance and psychological problems [4][5][6]. In adulthood, sleep deprivation is a risk factor of cardiovascular diseases [7].…”
Section: Introductionmentioning
confidence: 99%